Migrant women’s engagement in health-promotive activities through a women’s health collaboration - Lindsjö, Cecilia; Sjögren Forss, Katarina; Kumlien, Christine; Kottorp, Anders; Rämgård, Margareta (Frontiers in Public Health, 2023)
Introduction Social determinants of health impact health, and migrants are exposed to an inequitable distribution of resources that may impact their health negatively, leading to health inequality and social injustice. Migrant women are difficult to engage in health-promotional activities because of language barriers, socioeconomic circumstances, and other social determinants. Based on the framework of Paulo Freire, a community health promotion program was established in a community-academic partnership with a community-based participatory research approach. Aim The aim of this study was to describe how a collaborative women’s health initiative contributed to migrant women’s engagement in health promotion activities. Materials and methods This study was part of a larger program, carried out in a disadvantaged city area in Sweden. It had a qualitative design with a participatory approach, following up on actions taken to promote health. Health-promotional activities were developed in collaboration with a women’s health group, facilitated by a lay health promoter. The study population was formed by 17 mainly Middle Eastern migrant women. Data was collected using the story-dialog method and the material was analyzed using thematic analysis. Result Three important contributors to engagement in health promotion were identified at an early stage of the analysis process, namely, the group forming a social network, the local facilitator from the community, and the use of social places close to home. Later in the analysis process, a connection was made between these contributors and the rationale behind their importance, that is, how they motivated and supported the women and how the dialog was conducted. This therefore became the designated themes and were connected to all contributors, forming three main themes and nine sub-themes. Conclusion The key implication was that the women made use of their health knowledge and put it into practice. Thus, a progression from functional health literacy to a level of critical health literacy may be said to have occurred.